Single-cell droplet microfluidics for biomedical applications. Issue 11 (4th May 2022) - Liu, Dan; Sun, Meilin; Zhang, Jinwei; Hu, Rui; Fu, Wenzhu; Xuanyuan, Tingting; Liu, Wenming
Abstract : This review focuses on the recent advances in the fundamentals of single-cell droplet microfluidics and its applications in biomedicine, providing insights into design and establishment of single-cell microsystems and their further performance. Abstract : Single-cell manipulation and analysis is critical to the study of many fundamental biological processes and uncovering cellular heterogeneity, and presents the potential for extremely valuable applications in biomedical fields, including neuroscience, regenerative therapy, early diagnosis, and drug screening. The use of microfluidic technologies in single-cell manipulation and analysis is one of the most promising approaches and enables the creation of innovative conditions that are impractical or impossible to achieve using conventional methods. Herein, an overview of the technological development of single-cell droplet microfluidics is presented. The significant advantages of microfluidic droplet technology, the dynamic parameters affecting droplet production, and the geometric structures of microfluidic devices are emphasized. Furthermore, the progress to date in passive and active droplet generation methods based on microfluidics and various microfluidic tools for the production of single-cell droplets and hydrogel microspheres are summarized. Their key features, achievements, and limitations associated with single-cell droplet and hydrogel formation are discussed. The recent popularized applications of single-cell droplet microfluidics in biomedicine involving small-molecule detection, protein analysis, and drug screening and genetic analysis of single cells are explored too. Finally, the challenges that must be overcome to enable future applications in single-cell droplet microfluidics are highlighted.